Potential role of ACE2-related microRNAs in COVID-19-associated nephropathy (2020)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is responsible for coronavirus disease (COVID-19), potentially have severe kidney adverse effects. This organ expressed angiotensin-converting enzyme 2 (ACE2), the transmembrane protein which facilitate the entering of the virus into the cell. Therefore, early detection of the kidney manifestations of COVID-19 is crucial. Previous studies showed ACE2 role in various indications of this disease, especially in kidney effects. The MicroRNAs (miRNAs) in this organ affected ACE2 expression. Therefore, this review aims at summarizing the literature of a novel miRNA-based therapy and its potential applications in COVID-19-associated nephropathy. Furthermore, previous studies were analyzed for the kidney manifestations of COVID-19 and the miRNAs role that were published on the online databases, namely MEDLINE (PubMed) and Scopus. Several miRNAs, particularly miR-18 (which was upregulated in nephropathy), played a crucial role in ACE2 expression. Therefore, the antimiR-18 roles were summarized in various primate models that aided in developing the therapy for ACE2 related diseases.